Analisis Sambungan Balok-Kolom Beton Bertulang Dengan Pemodelan Numerik Berbasis Metode Elemen Hingga: The Beam-Column Reinforced Concrete Connection Analysis In Numerical Modeling Based On The Finite Element Method - Aminullah Aminullah; Miftahul Iman (Media Ilmiah Teknik Sipil, 2022)
A Damage to the reinforced concrete beam-column connection system had found in buildings such as residential buildings, houses of worship, and so on. This was caused by an incidental changed in the position of the beam elevation at the beam-column connection. The research had modelled the reinforced concrete beam-column connection with variations beam elevation, successively: h; 2h; and 3h where h was the height of the column. Modeling used 3D frame idealization and 3D solids element. The idealization of 3D frames had used to evaluate the capacity of the beam-column due to the beam elevation changed. T. The results showed that due to beam elevation chnaged had significant increased in the moment and shear capacity. The percentage increased in moment and shear respectively were 15%, 35%, and 45% of the control beam-column. The most severe cracks were occurred when the beam elevation was at 1.00hb. The percentage of beam-column connection stress concentration is 8,74% (CM); 9.80% (0.25hb); 11.09%(0,50hb); 12.13%(0.75hb); and 13.41% (1.00hb) for the ratio of horizontal and vertical stresses (S11/S22) on concrete frames. The percentage of stress concentration in steel reinforcement is 4.15% (CM); 4.47%(0.25hb); 5.25%(0,50hb); 4.56%(0.75hb); and 4.57%(1.00hb) for the comparison of von Mises and horizontal stresses (SVM/S11)